1997
DOI: 10.1086/303461
|View full text |Cite
|
Sign up to set email alerts
|

Zero‐Energy Rotating Accretion Flows near a Black Hole

Abstract: We characterize the nature of thin, axisymmetric, inviscid, accretion flows of cold adiabatic gas with zero specific energy in the vicinity of a black hole by the specific angular momentum. Using two-dimensional hydrodynamic simulations in cylindrical geometry, we present various regimes in which the accretion flows behave distinctly differently. When the flow has a small angular momentum (λ < ∼ λ b ), most of the material is accreted into the black hole forming a quasi-spherical flow or a simple disk-like str… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
150
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 143 publications
(154 citation statements)
references
References 30 publications
4
150
0
Order By: Relevance
“…This is also the centrifugal pressure supported boundary layer (or, CENBOL) which behaves as a Compton cloud in the Chakrabarti & Titarchuk (1995) model of two component accretion flow (TCAF). According to the numerical simulations of the sub-Keplerian (lowangular momentum) accretion which includes the dynamical cooling (Ryu et al, 1997) or the thermal cooling (Molteni et al, 1996;Chakrabarti et al, 2004), the frequency of the shock oscillation is similar to the observed QPO frequency for BHCs. Thus, the instantaneous QPO frequency ν QPO (in s −1 ) is expected to be…”
Section: Evolution Of Qpo Frequency and Its Modeling By Pos Solutionmentioning
confidence: 53%
See 1 more Smart Citation
“…This is also the centrifugal pressure supported boundary layer (or, CENBOL) which behaves as a Compton cloud in the Chakrabarti & Titarchuk (1995) model of two component accretion flow (TCAF). According to the numerical simulations of the sub-Keplerian (lowangular momentum) accretion which includes the dynamical cooling (Ryu et al, 1997) or the thermal cooling (Molteni et al, 1996;Chakrabarti et al, 2004), the frequency of the shock oscillation is similar to the observed QPO frequency for BHCs. Thus, the instantaneous QPO frequency ν QPO (in s −1 ) is expected to be…”
Section: Evolution Of Qpo Frequency and Its Modeling By Pos Solutionmentioning
confidence: 53%
“…One satisfactory model namely shock oscillation model (SOM) by Chakrabarti and his collaborators (Molteni et al, 1996), shows that the oscillation of X-ray intensity could be due to the oscillation of the post-shock (Comptonizing) region. According to SOM, shock wave oscillates either because of resonance (where the cooling time scale of the flow is comparable to the infall time scale; (Molteni et al, 1996)) or because the Rankine-Hugoniot condition is not satisfied (Ryu et al, 1997) to form a steady shock. The QPO frequency is inversely proportional to the infall time (t in f all ) in the post-shock region.…”
Section: Evolution Of Qpo Frequency and Its Modeling By Pos Solutionmentioning
confidence: 99%
“…The monotonically increasing frequency (starting from 102 mHz observed on March 22 to 5.69 Hz observed on April 17) as in GRO J1655-40 and XTE J1550-564 (CDNP08, CDP09) motivated us to fit it with the same POS solution as used in CDNP08 and CDP09. In this solution, at the onset of the outburst, a shock wave moves toward the black hole, which oscillates either because of resonance (cooling time ∼ infall time; Molteni et al 1996) or because of the fact that the Rankine-Hugoniot relation is not satisfied (Ryu et al 1997) to form a steady shock. The QPO frequency is obtained from the inverse of the in-fall time scale from the post-shock region.…”
Section: Timing Analysismentioning
confidence: 99%
“…The almost constancy of angular momentum comes into being primarily because, as has been shown by extensive work done earlier (Chakrabarti 1996a), the viscosity timescale t visc ∼ r 2 /ν s is much longer than the infall time scale r 3/2 /(GM) 1/2 , ν s being the kinematic viscosity. It was shown by Molteni et al (1996, hereafter referred to as MSC96) and Ryu et al (1997, hereafter RCM 1997) that these shocks may also oscillate in the presence of cooling. These oscillations are explained to be due to a resonance between the dominant cooling time scale and the infall time scale, and the cooling could be due to thermal/non-thermal radiative effects (as in MSC96), or to dynamical cooling due to outflows (as in RCM97) or both.…”
Section: Introductionmentioning
confidence: 99%